Preparation method of high-performance aluminum-based composite material

By using high-purity copper powder and lignin powder as precursors for the reinforced phase, copper clad lignin reinforced phase powder was prepared and hot-pressed and sintered with aluminum powder, the problem of improving the mechanical and electrical properties of existing aluminum-based composite materials was solved, and significant mechanical properties improvement and electrical properties maintenance were achieved, while avoiding defects in graphene materials.

CN119824268APending Publication Date: 2025-04-15FAR EAST CABLE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510024914.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

There is room for improvement in the mechanical and electrical properties of existing aluminum-based composite materials. At the same time, the easy agglomeration, complex process and expensive problems of graphene materials limit their engineering applications.

Method used

High-purity copper powder and lignin powder are used as precursors for the reinforced phase, and copper clad lignin reinforced phase powder is prepared through ultrasonic oscillation dispersion, ball milling and pyrolysis conversion processes, and variable speed ball milling and hot pressing sintering with aluminum powder to form a high-performance aluminum-based composite material.

Benefits of technology

The mechanical and electrical properties of aluminum-based composite materials have been significantly improved, the tensile strength is increased by about 20%, and the Vickers hardness is increased by about 17%, while maintaining cost-effectiveness, avoiding the easy agglomeration and expensive price problems of graphene materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824268A_ABST
    Figure CN119824268A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-performance aluminum-based composite material, according to the method, high-purity copper powder and a lignin precursor are used as reinforcing phases, the good dispersity of lignin in an aluminum matrix and the interface bonding performance of copper cladding are improved, in the preparation process, firstly, a solvent is used for conducting ultrasonic concussion pre-dispersion on the lignin, and then the high-performance aluminum-based composite material is obtained; the preparation method comprises the following steps: dispersing copper powder into a solution, carrying out ball milling on the dispersed solution and the copper powder, carrying out drying treatment after the ball milling process is finished to obtain copper-coated lignin reinforced phase powder, mixing the reinforced phase powder and aluminum powder according to a certain ratio through variable-speed ball milling to prepare copper-coated lignin reinforced aluminum composite powder, carrying out pyrolysis conversion on the mixed powder, and carrying out high-speed ball milling to prepare the copper-coated lignin reinforced aluminum composite powder. And carrying out hot pressed sintering to obtain the aluminum-based composite material. The mechanical property and the electrical property of the aluminum-based composite material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of metal composite materials, and in particular to a method for preparing a high-performance aluminum-based composite material. Background Art

[0002] Since the 1960s, metal matrix composites have received extensive attention and developed rapidly, among which aluminum matrix composites have developed the most extensively and rapidly. Aluminum matrix composites have become an important composite material among metal matrix composites due to their excellent properties such as light weight, high specific strength, low thermal expansion coefficient, and easy processing, and are widely used in civilian and military fields. Common ones include fiber-reinforced aluminum matrix composites and particle-reinforced aluminum matrix composites. The enhancement effect of reinforcements such as silicon carbide, boron carbide and aluminum oxide on the comprehensive performance of the material needs to be improved, and the plasticity is greatly reduced, which limits the application of composite materials.

[0003] Since graphene was prepared in 2004, compared with traditional reinforcements, graphene has the advantages of low density, high mechanical properties, good thermal conductivity and low thermal expansion coefficient, and has been considered as a very promising reinforcement since its birth. Adding it to an aluminum matrix can improve the mechanical and electrical properties of the aluminum matrix. For example, the Chinese invention patent with the authorization announcement number CN108941547B and the Chinese invention application with the application publication number CN117821795A both disclose an aluminum-based composite material with graphene as a reinforcement. Although the prior art can prepare aluminum-based composite materials with excellent performance, due to the problems that graphene materials are very easy to agglomerate, complex process and expensive. Therefore, the engineering application of directly adding graphene to metal-based conductor composite materials is greatly restricted. Summary of the invention

[0004] The purpose of the present invention is to propose a method for preparing a high-performance aluminum-based composite material in view of the deficiencies in the prior art, which can significantly improve the mechanical properties of the aluminum-based composite material and regulate the electrical properties of the aluminum-based composite material while maintaining cost-effectiveness.

[0005] The technical solution to achieve the purpose of the present invention is:

[0006] A method for preparing a high-performance aluminum-based composite material, using high-purity copper powder and lignin powder as precursors of a reinforcement phase to prepare the aluminum-based composite material, specifically comprising the following steps:

[0007] Step S1: weighing lignin powder with a mass fraction of 0.3% to 0.6%, placing it in an ultrasonic cleaning machine, adding a solvent for ultrasonic oscillation dispersion, and forming a mixed solution containing lignin;

[0008] Step S2: putting the mixed solution containing lignin and copper powder into a ball milling tank, and performing ball milling to obtain a mixed slurry containing lignin and copper;

[0009] Step S3: drying the mixed slurry containing lignin and copper powder to obtain copper-coated lignin reinforcement phase powder;

[0010] Step S4: Weighing 0.4-0.6% copper-coated lignin reinforcement phase powder, and subjecting it to variable speed ball milling with aluminum powder to obtain composite powder;

[0011] Step S5: placing the composite powder into a mold for pre-pressing, and pyrolyzing and converting it to obtain an aluminum-based composite material, followed by sintering to obtain an aluminum-based composite block, and cooling it in the furnace to complete the preparation.

[0012] Furthermore, the lignin powder is extracted from pine wood by using a DES low eutectic solvent extraction method and has a diameter of 50 to 100 nm.

[0013] Furthermore, the solvent in step S1 is industrial pure ethanol solution.

[0014] Furthermore, in step S2, the ball milling time is 4 to 6 hours, the rotation speed is 150 to 250 r / min, and the ball to material ratio is (4 to 7):1.

[0015] Furthermore, in the step S4, stearic acid with a mass fraction of 0.4-0.6% is added during the ball milling process.

[0016] Furthermore, in step S4, ball milling is carried out under the protection of inert gas throughout the whole process, the ball milling time is 4 to 6 hours, the initial rotation speed is 150 to 250 r / min, and the speed is changed to 250 to 350 r / min in the last half hour, and the ball-to-material ratio is maintained at (4 to 6):1.

[0017] Furthermore, the inert gas is argon.

[0018] Furthermore, in step S5, the pre-loading load is 4-6 kN.

[0019] Furthermore, in step S5, the composite powder is pyrolyzed and converted in a vacuum hot pressing sintering furnace, the vacuum degree is not greater than 2×10-2Pa, the temperature is 400-700°C, and the time is 0.5-1.5 hours to complete the pyrolysis conversion process of lignin;

[0020] Furthermore, in the step S5, sintering is performed in a vacuum hot pressing sintering furnace at a temperature of 500-700° C. and a pressure of 25-35 MPa, and the temperature and pressure are maintained for 2-4 hours to complete the preparation process of the aluminum-based composite block.

[0021] By adopting the above technical solution, the present invention has the following beneficial effects:

[0022] (1) The preparation method of the present invention uses copper powder and lignin precursor reinforcement phase, utilizes the good dispersibility of lignin in the aluminum matrix, and adopts the lignin copper coating process to achieve good interface bonding performance, thereby improving the mechanical properties and electrical properties of the aluminum-based composite material.

[0023] (2) The preparation method of the present invention significantly improves the comprehensive mechanical properties of aluminum-based materials and maintains good electrical properties of aluminum-based materials, with the electrical properties being basically the same as those of pure aluminum, with the tensile strength of 4% pure aluminum increased by about 20%, and the Vickers hardness increased by about 17% compared with pure aluminum, by adding a nano-lignin precursor and optimizing the pyrolysis conversion, preparation process and anti-oxidation method during the preparation process. The problems of easy agglomeration and high price of graphene materials are avoided. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below based on specific embodiments and in conjunction with the accompanying drawings, wherein:

[0025] Figure 1 This is an electron microscope image of copper-coated lignin powder;

[0026] Figure 2 This is the EDS image of copper-coated lignin powder;

[0027] Figure 3 This is an electron microscope image of aluminum-based composite powder containing copper-coated lignin precursor;

[0028] Figure 4 EDS image of aluminum-based composite powder containing copper-coated lignin precursor

[0029] Figure 5 Actual photo of the sintered sample of the new aluminum-based composite material. DETAILED DESCRIPTION

[0030] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0031] (Example 1)

[0032] This embodiment provides a method for preparing a high-performance aluminum-based composite material, which uses high-purity copper powder and lignin precursor as reinforcing phases to increase the good dispersibility of lignin in the aluminum matrix and the interface bonding performance of the copper coating. Combined with the precisely controlled ball milling and pyrolysis conversion and hot pressing sintering process, the mechanical properties of the material are significantly improved and the electrical properties of the material are regulated. Specifically, the following steps are included:

[0033] Step S1: high-purity copper powder produced by Guangzhou Metal Metallurgy Co., Ltd. is used as the copper-clad material, with a particle size of 20 μm and a purity of 99.99%. The lignin used is extracted from pine wood using the DES low-eutectic solvent extraction method, with a diameter of 50 to 100 nm. The matrix material is high-purity aluminum powder provided by Beijing Yi Jin New Materials Technology Co., Ltd., with a particle size of 10 μm and a purity of 99.9%.

[0034] Weigh 0.5% lignin powder by mass, place it in an ultrasonic cleaning machine, add industrial pure ethanol solution and perform ultrasonic oscillation for 30 minutes to achieve full dispersion and form a mixed solution containing lignin.

[0035] Step S2: The mixed solution containing lignin and ethanol and 0.5% copper powder by mass are put into a BM-40 planetary ball mill for ball milling. The ball milling time is set to 5 hours, the rotation speed is 200r / min, and the ball-to-material ratio is maintained at 5:1 to obtain a mixed slurry containing lignin and copper.

[0036] Step S3: Dry the mixed slurry containing lignin and copper in a vacuum drying oven to obtain copper-coated lignin reinforced phase powder. The electron microscope image and EDS surface scan are as follows: Figure 1 and 2 As shown in the figure, it can be seen that the composite powder is composed of copper and C elements, and the lignin and copper powder are interlocked with each other to obtain copper-coated lignin powder.

[0037] Step S4: Weigh 0.5% copper-coated lignin powder and aluminum powder for variable speed ball milling, and add 0.5% stearic acid to prevent powder adhesion or cold welding. Under argon protection, ball milling for 6 hours, the initial speed is set to 200r / min, and the speed is increased to 300r / min in the last half hour, keeping the ball-to-material ratio at 5:1, to obtain aluminum-based composite powder containing copper-coated lignin precursor, SEM and EDS analysis diagrams are shown as follows Figure 3 and 4 As shown in the figure, it can be seen that the aluminum-based composite powder containing the copper-coated lignin precursor has good dispersion, and aluminum, C and copper elements are distributed, which shows that the interface bonding between the copper-coated lignin powder and the aluminum powder is good.

[0038] Step S5: The composite powder is placed in a mold for pre-compression with a pre-compression load of 5 kN. Afterwards, the composite powder is pyrolyzed and converted in a ZTY-40-20 vacuum hot pressing sintering furnace with a vacuum environment of 2×10 -2 Pa, the conversion temperature was 600 ° C, the time was 1 hour, and the pyrolysis conversion was completed to obtain an aluminum-based composite material; then, the vacuum degree was 2×10 -2Pa vacuum environment, the aluminum-based composite material was kept in a sintering furnace for 3 hours, and hot-pressed at a temperature of 600 ° C and a pressure of 30 MPa to obtain an aluminum-based composite block, which was then cooled in the furnace to complete the preparation. The sintered sample is shown in the figure. Figure 5 shown.

[0039] (Example 2)

[0040] The preparation method of this embodiment is similar to that of embodiment 1, except that:

[0041] When pyrolysis conversion is performed, the conversion temperature is 400°C and the time is 1.5 hours;

[0042] When hot pressing sintering is performed, the temperature is 500°C, the pressure is 25MPa, and the temperature and pressure are maintained for 4 hours.

[0043] (Example 3)

[0044] The preparation method of this embodiment is similar to that of embodiment 1, except that:

[0045] When pyrolysis conversion is performed, the conversion temperature is 700°C and the time is 0.5 hours;

[0046] When hot pressing sintering is performed, the temperature is 700°C, the pressure is 35MPa, and the temperature and pressure are maintained for 2 hours.

[0047] (Comparative Example 1)

[0048] The preparation method of this embodiment is similar to that of Embodiment 1, except that the pyrolysis conversion and hot pressing sintering are not performed under vacuum.

[0049] (Comparative Example 2)

[0050] The preparation method of this embodiment is similar to that of embodiment 1, except that:

[0051] When pyrolysis conversion is performed, the conversion temperature is 500°C and the time is 2 hours;

[0052] When hot pressing sintering is performed, the temperature is 600°C, the pressure is 40MPa, and the temperature and pressure are maintained for 1 hour.

[0053] (Comparative Example 3)

[0054] The preparation method of this embodiment is similar to that of embodiment 1, except that:

[0055] When pyrolysis conversion is performed, the conversion temperature is 380°C and the time is 2 hours;

[0056] When hot pressing sintering is performed, the temperature is 480°C, the pressure is 40MPa, and the temperature and pressure are maintained for 5 hours.

[0057] (Comparative Example 4)

[0058] The preparation method of this embodiment is similar to that of embodiment 1, except that:

[0059] When pyrolysis conversion is performed, the conversion temperature is 720°C and the time is 0.5 hours;

[0060] When hot pressing sintering is performed, the temperature is 720°C, the pressure is 40MPa, and the temperature and pressure are maintained for 1.5 hours.

[0061] (Comparative Example 5)

[0062] The preparation method of this embodiment is similar to that of embodiment 1, except that:

[0063] When pyrolysis conversion is performed, the conversion temperature is 720°C and the time is 0.5 hours;

[0064] When hot pressing sintering is performed, the temperature is 720°C, the pressure is 20MPa, and the temperature and pressure are maintained for 2 hours.

[0065] The aluminum-based composite blocks of the above embodiments and comparative examples were tested for performance and compared with pure aluminum blocks. The results are as follows:

[0066] Material Tensile strength / MPa Hardness / HV Electrical conductivity / IACS% Pure aluminum 151 56.27 53.80 Example 1 180 66.01 59.18 Example 2 169 61.63 57.24 Example 3 176 71.12 54.37 Comparative Example 1 135 52.01 47.11 Comparative Example 2 157 63.24 52.28 Comparative Example 3 142 50.88 54.13 Comparative Example 4 167 58.23 55.81 Comparative Example 5 171 57.79 56.32

[0067] As can be seen from the table, compared with pure aluminum, the aluminum-based composite material prepared by the preparation method of this embodiment has the best comprehensive performance improvement in Example 1, with electrical properties increased from 53.80IACS% to 59.18IACS%, tensile properties increased from 151MPa to 180MPa, and hardness increased from 56.27HV to 66.01HV. The performance of the material in Comparative Example 1 is seriously reduced. Failure to sinter in a vacuum environment will lead to oxidation of the matrix and will produce harmful interfacial reactions with the lignin reinforcement phase, resulting in a decrease in the overall performance of the material. From the perspective of Comparative Examples 2-5, for the conversion temperature, at the appropriate temperature and time, the conversion efficiency of lignin can reach the highest, so that it can fully play its role in the matrix and improve the comprehensive performance. For the sintering temperature, the appropriate sintering temperature can make the material form a small and uniform grain structure. For the insulation time, too long insulation time will cause excessive growth of the grains, thereby reducing the mechanical properties of the material. This is because long-term high-temperature treatment allows the grains to have enough time to recrystallize and grow, resulting in an increase in grain size, which in turn affects the hardness and strength of the material; insufficient holding time will result in insufficient sintering density of the material, which will also lead to a decrease in material performance. For sintering pressure, appropriate pressure helps to increase the density of the material, reduce porosity, and thus improve the overall performance of the material. Too high or too low pressure may lead to adverse results. Too high pressure may cause the crushing of the reinforcing particles or plastic deformation of the aluminum matrix, while too low pressure cannot achieve sufficient densification effect.

[0068] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-performance aluminum-based composite material, characterized in that: Using high-purity copper powder and lignin powder as precursors of the reinforcement phase to prepare an aluminum-based composite material specifically includes the following steps: Step S1: weighing lignin powder with a mass fraction of 0.3% to 0.6%, placing it in an ultrasonic cleaning machine, adding a solvent for ultrasonic oscillation dispersion, and forming a mixed solution containing lignin; Step S2: putting the mixed solution containing lignin and copper powder into a ball milling tank, and performing ball milling to obtain a mixed slurry containing lignin and copper powder; Step S3: drying the mixed slurry containing lignin and copper to obtain copper-coated lignin reinforcement phase powder; Step S4: Weighing 0.4-0.6% copper-coated lignin reinforcement phase powder, and subjecting it to variable speed ball milling with aluminum powder to obtain composite powder; Step S5: placing the composite powder into a mold for pre-pressing, and pyrolyzing and converting it to obtain an aluminum-based composite material, followed by sintering to obtain an aluminum-based composite block, and cooling it in the furnace to complete the preparation.

2. The method for preparing a high-performance aluminum-based composite material according to claim 1, characterized in that: The lignin powder is extracted from pine wood by using a DES low eutectic solvent extraction method and has a diameter of 50 to 100 nm.

3. The method for preparing a high-performance aluminum-based composite material according to claim 1, characterized in that: The solvent in step S1 is industrial pure ethanol solution.

4. The method for preparing a high-performance aluminum-based composite material according to claim 1, characterized in that: In the step S2, the ball milling time is 4 to 6 hours, the rotation speed is 150 to 250 r / min, and the ball to material ratio is (4 to 7):

1.

5. The method for preparing a high-performance aluminum-based composite material according to claim 1, characterized in that: In the step S4, stearic acid with a mass fraction of 0.4-0.6% is added during the ball milling process.

6. The method for preparing a high-performance aluminum-based composite material according to claim 1, characterized in that: In step S4, ball milling is performed under the protection of inert gas throughout the process, the ball milling time is 4 to 6 hours, the initial rotation speed is 150 to 250 r / min, and the speed is changed to 250 to 350 r / min in the last half hour, and the ball-to-material ratio is maintained at (4 to 6):

1.

7. The method for preparing a high-performance aluminum-based composite material according to claim 6, characterized in that: The inert gas is argon.

8. The method for preparing a high-performance aluminum-based composite material according to claim 1, characterized in that: In the step S5, the pre-loading load is 4-6 kN.

9. The method for preparing a high-performance aluminum-based composite material according to claim 1, characterized in that: In step S5, the composite powder is pyrolyzed and converted in a vacuum hot pressing sintering furnace, and the vacuum degree is not greater than 2×10 -2 Pa, the temperature is 400-700°C, and the time is 0.5-1.5 hours to complete the pyrolysis conversion process of lignin.

10. The method for preparing a high-performance aluminum-based composite material according to claim 1, characterized in that: Place In step S5, the sintering is carried out in a vacuum hot pressing sintering furnace at a temperature of 500-700° C. and a pressure of 25-35 MPa. Continue to keep the temperature and pressure for 2-4 hours to complete the preparation process of the aluminum-based composite block.

Citation Information

Patent Citations

  • A method for preparing copper-doped graphene-reinforced aluminum-based composite materials

    CN108941547B

  • Preparation method of net-structure low-damage graphene and silicon carbide hybrid reinforced aluminum-based composite material

    CN117821795A